2006
DOI: 10.1111/j.1600-0536.2006.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservatives sensitivity in Israel: a 10‐year overview (1995–2004)

Abstract: This study presents a 10-year survey of 2285 patients tested to common preservatives in northern Israel. The demographic and clinical data were analysed using a revised MOAHLFA index. Patch testing was based on the International Contact Dermatitis Research Group (ICDRG) guidelines. 411 (18%) patients were found to have positive reactions to 1 or more preservatives. The most frequent allergens tested positively were thimerosal, methylchloroisothiazolinone/methylisothiazolinone (MCI/MI), and formaldehyde. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…The sensitization rates of DMDM hydantoin (aqueous and non-aqueous), imidazolidinyl urea (non-aqueous), and diazolidinyl urea (aqueous and non-aqueous), which are also formaldehyde releasers, remained stable since 1992, as found by Zoller and colleagues (22). The significant increase in positive reactions to the aqueous form of imidazolidinyl urea from 1984 to 2002 (p ¼ 0.002) may have contributed to the increase in positive reactions to formaldehyde; increased use patterns may have also been responsible.…”
Section: Preservatives and Stabilizersupporting
confidence: 52%
See 3 more Smart Citations
“…The sensitization rates of DMDM hydantoin (aqueous and non-aqueous), imidazolidinyl urea (non-aqueous), and diazolidinyl urea (aqueous and non-aqueous), which are also formaldehyde releasers, remained stable since 1992, as found by Zoller and colleagues (22). The significant increase in positive reactions to the aqueous form of imidazolidinyl urea from 1984 to 2002 (p ¼ 0.002) may have contributed to the increase in positive reactions to formaldehyde; increased use patterns may have also been responsible.…”
Section: Preservatives and Stabilizersupporting
confidence: 52%
“…The positivity rate ranged from 4% in 1970 to 9.3% in 1998. Zoller and colleagues showed a similar increase during their study period, but their rate was lower (from 0.3% in 1995 to 1.9% in 2004) (22). Similarly, the quaternium-15 sensitivity rate, a formaldehyde releaser that is widely used, significantly increased from 1976 to 2002, as shown by Nguyen and colleagues (12).…”
Section: Preservatives and Stabilizermentioning
confidence: 54%
See 2 more Smart Citations
“…In case-control studies, Hg exposure (measured as total Hg in urine) has been associated with increased risk of lupus(Cooper et al, 2004)and greater severity of scleroderma (Arnett et al, 1996). Thimerosal has been shown to be a potent allergen in human populations, with a relatively high prevalence of allergic individuals in populations worldwide(Pratt et al, 2004; Slodownik and Ingber, 2005; Wetter et al, 2005; Zoller et al, 2006; Zug et al, 2008). We have reported that environmental and occupational exposures to elemental and iHg are positively correlated with serum levels of autoantibodies (Gardner et al, 2010; Silva et al, 2004).…”
Section: Introductionmentioning
confidence: 99%